La introducción del liberalismo inglés en Barcelona: "Lo bello y lo sublime", de Manuel Casamada: The Introduction of English Liberalism in Barcelona: Manuel Casamada’s The Beautiful and the Sublime - Roviró Alemany, Ignasi (Studium, 2018)
ResumenA principios del siglo xixlos literatos de la capital de España estaban divididos en dos facciones: una progresista y otra conservadora. Estas posiciones ideológicas contaminaron la literatura. Los progresistas utilizaron como bandera un texto retórico del predicador escocés Hugo Blair (1718-1800); los conservadores, un texto del esteta francés Charles Batteux (1713-1780). El uso de Blair representó también una vía más de introducción del pensamiento liberal inglés y la divulgación de Edmund Burke, de especial interés para la oposición entre lo bello y lo sublime. Hasta ese momento, los conceptos de lo bello y lo sublime se entendían como conceptos encadenados. En Barcelona, la influencia de Blair se ve en la obra del fraile liberal Manuel Casamada (1772-1841) y en el discurso, inédito, que pronunció en la Real Academia de Buenas Letras de Barcelona (1837), que ha sido incluido, transcrito y anotado, en este artículo.Palabras clave: Hugo Blair, Manuel Casamada, bello, sublime, estética AbstractIn early nineteenth century, the writers of the capital of Spain were divided into two factions: one conservative and one progressive. These ideological positions were transferred to literature. The progressives used as flag a rhetorical text of the Scottish preacher Hugh Blair (1718-1800), the conservatives, a text of the French esthete Charles Batteux (1713-1780). Blair’s use represents one route of introduction of liberal English thought and the popularization of Edmund Burke, work of particular interest to the opposition between the beautiful and the sublime. Until then, the concepts of beauty and the sublime understood as linked concepts. In Catalonia, Blair's influence is seen in the work of the Liberal priest Manuel Casamada (1772-1841) and in the speech, unedited, who spoke at the Real Acadèmia de Bones Lletres de Barcelona(1837), which has been included, transcribed and annotated, in this article.Key words: Hugh Blair, Manuel Casamada, beautiful, sublime, aesthetic